The relationship between nutritional intake and diet with obesity in adolescents - Hikmawati Mas'ud; Asmarudin Pakhri; Abdullah Tamrin; Sitti Saharia Rowa (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
The prevalence of obesity in adolescents continues to increase along with the increase in social welfare. This is due to the increasing consumption of energy and instant food. Obesity in adolescents can interfere with learning activities and can continue into adulthood. This study aims to find the relationship between nutritional intake and diet with obesity in adolescents. .The research location is in SMAN 21 and MAN 3 Makassar because in these schools there are quite high obesity sufferers. The location of the school was chosen purposively. The population is all obese students in the school. The sample is 42 obese students with a BMI of 25 and above and non-obese students who come from both schools and are still actively learning. Data collection of energy and nutrient intake using questionnaires and recall forms for adolescents. Data on weight and height of adolescents were collected using digital scales and microtois. Data analysis with chisquare test.The results of this study found that there was no relationship between energy and nutrient intake with obesity in adolescents. However, there is a relationship between the frequency of consumption of vegetables, snacks and drinking water with adolescent obesity, with a P value <0.05. This means that obese people need to eat vegetables and drink more water and limit their snacks to lose weight. The research is expected to continue with nutritional care for obese adolescents to lose weight.Keywords: nutritional intake, diet and adolescent obesityReferrence : 13 (2012-2020)